2018
DOI: 10.1103/physrevlett.120.057405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetooptics of Exciton Rydberg States in a Monolayer Semiconductor

Abstract: We report 65 tesla magneto-absorption spectroscopy of exciton Rydberg states in the archetypal monolayer semiconductor WSe2. The strongly field-dependent and distinct energy shifts of the 2s, 3s, and 4s excited neutral excitons permits their unambiguous identification and allows for quantitative comparison with leading theoretical models. Both the sizes (via low-field diamagnetic shifts) and the energies of the ns exciton states agree remarkably well with detailed numerical simulations using the non-hydrogenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

45
271
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(325 citation statements)
references
References 45 publications
(61 reference statements)
45
271
4
Order By: Relevance
“…If we assume the 0.8meV linewidth difference is mostly due to faster population decay, and take the 1s luminescence decay time to be 2ps from a recent study [35], we infer a 2s lifetime of about 0.6ps. Further the 2s oscillator strength is about 15 times weaker than 1s from absorption spectra in Fig.1, consistent with the value from a recent diamagnetic shift measurement [36], while the low temperature 1s intensity is about 60 times stronger than 2s (Fig.1c). This suggests a decay rate ratio of 4, in reasonable agreement with the above estimation from linewidth difference.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…If we assume the 0.8meV linewidth difference is mostly due to faster population decay, and take the 1s luminescence decay time to be 2ps from a recent study [35], we infer a 2s lifetime of about 0.6ps. Further the 2s oscillator strength is about 15 times weaker than 1s from absorption spectra in Fig.1, consistent with the value from a recent diamagnetic shift measurement [36], while the low temperature 1s intensity is about 60 times stronger than 2s (Fig.1c). This suggests a decay rate ratio of 4, in reasonable agreement with the above estimation from linewidth difference.…”
supporting
confidence: 78%
“…For the 1s exciton this is given approximately by 1/ 2 , where 36] is the exciton Bohr radius. In the case of 2s excitons, a recent measurement found that the electron-hole separation in 2s is about 6.6nm [36]. Assuming that the 1s and 2s excitons have about the same mass, the 2s exchange interaction is then about 15 times weaker.…”
mentioning
confidence: 99%
“…S1. Monolayer WSe2 hosts a rich spectrum of excitonic species [23][24][25][26][27][28] . Several previously identified excitonic states are indicated in the figure, including the neutral bright exciton ( 0 ), bright trions ( ± ) [29][30][31][32][33] , the intravalley spinforbidden dark exciton ( 0 ) 17-20, 34 , and dark trions ( ± ) 18, 35 .…”
Section: Maintextmentioning
confidence: 99%
“…For the coupling between 2d carriers and environmental phonons in WSe 2 , the band structure around the K-point is approximated by electron and hole effective masses m e = m h = 0.4m 0 yielding a reduced exciton mass µ r = 0.2m 0 . [42] We limit carrier-phonon scattering to intra-valley processes neglecting coupling to dark excitons that involve large momentum transfer q. [32] This is justified by the 1/q-scaling behavior of the Fröhlichtype coupling considered here.…”
mentioning
confidence: 99%
“…[32] This is justified by the 1/q-scaling behavior of the Fröhlichtype coupling considered here. We use a layer thickness of h 2d = 0.66 nm, a dielectric constant ε 2d = 14.6 corresponding to a screening length r 0 = 4.5 nm [42] and a broadening Γ = 10 meV. For the inter-layer distance, we choose h int = 0.2 nm.…”
mentioning
confidence: 99%